Prognostic implications of venous invasion in pancreatic cancer following radical surgical resection: a pathological perspective - Jin-Can Huang; Cheng-Run Zhang; Han-Xuan Wang; Shao-Cheng Lyu; Ren Lang; Tao Jiang (Frontiers in Medicine, 2025)
BackgroundThe assessment of resectability in borderline resectable pancreatic cancer (BRPC) primarily relies on preoperative imaging, which examines the spatial association between the tumor and adjacent vital veins, particularly the portal venous system. However, venous invasion detected via imaging is rarely confirmed by postoperative pathology. This research seeks to assess the long-term results in patients with pathologically verified venous invasion and to explore the related risk factors.MethodsThis study involved 248 individuals who underwent radical pancreaticoduodenectomy (PD) from January 2011 to July 2023. Patients were classified into three categories based on preoperative imaging and postoperative pathology: no venous invasion (n = 99), imaging-suspected (n = 30), and pathology-confirmed (n = 119). Clinical features and prognoses were compared among groups. In the cohort with pathology-confirmed venous invasion, patients were further classified by invasion depth into intimal (n = 51) and non-intimal (n = 68) subgroups for risk factor analysis.ResultsPatients with pathologically confirmed venous invasion exhibited significantly reduced disease-free survival (DFS) and overall survival (OS) when compared to those with either imaging-suspected or absent venous invasion (p < 0.001). Further analysis of pathology-confirmed venous invasion patients showed significantly lower DFS (p = 0.008) and OS (p < 0.001) compared to non-intimal invasion patients. Independent risk variables for poor DFS included age ≥60 years, tumor diameter >3 cm, and intimal invasion. Independent risk factors for poor OS in patients with venous invasion included age ≥60 years, poorly differentiated tumors, intimal invasion, and TNM stage III.ConclusionIntimal venous invasion emerged as a distinct risk factor influencing postoperative survival. Radical surgical resection remains essential for attaining favorable long-term outcomes in pancreatic cancers.